Perancangan Tata Letak Gudang pada CV. Sarana Graha Lestari - Wijaya Wardhana Gunawan; I Gede Agus Widyadana (Jurnal Titra, 2019)
CV. Sarana Graha Lestari is a company that distribute aluminium since 1991. CV. Sarana Graha Lestari problem about inventory arrangement in their warehouse therefore, the warehouse condition become messy and difficult for workers to takes materials. CV. Sarana Graha Lestari want to make an effective and efficient warehouse placement that make workers easier to search and takes materials. Two algorithm are introduced to arrange the layout. The first layout algorithm based on Stock Keeping Unit (SKU), the other based on groups of SKU. The result show that layout arrangement based on group of SKU has less moment and easier to search materials.